Aqueous self-assembly of short hydrophobic peptides containing norbornene amino acid into supramolecular structures with spherical shape. Issue 93 (21st September 2016) - Ruffoni, Alessandro; Cavanna, Maria V.; Argentiere, Simona; Locarno, Silvia; Pellegrino, Sara; Gelmi, Maria Luisa; Clerici, Francesca
Abstract : The preparation and self-assembly of short hydrophobic peptides containing the non-coded norbornene amino acid is reported. The formation of a supramolecular assembly in water was assessed by TEM and DLS. Abstract : The preparation and self-assembly of short hydrophobic peptides able to solubilize in water through the formation of supramolecular assembly is reported. The two diastereoisomeric pentapeptides AcAla-NRB-Ala-Aib-AlaNH2 1 and2 containing the two enantiomers of non-proteinogenic norbornene amino acid (NRB) were synthesized in an efficient way and in good yields. They were insoluble in organic solvent, except MeOH and DMSO, but completely soluble in water despite that they are made of hydrophobic amino acids. The formation of a supramolecular assembly in water was assessed by Transmission Electron Microscopy (TEM) and Dynamic Light Scattering (DLS) using1 and2 individually or in a mixture. Conformational analysis on the two diastereoisomers, performed in CD3 CN, CD3 OH and in H2 O/D2 O, indicated the formation of a stable 310 -helix structure for both peptides: the helix structure is more stable in CD3 CN and CD3 OH than in H2 O/D2 O where a helix/random coil transition was observed. Apparently, the norbornene moiety plays a role in the stabilization, in fact 1 R 2 R 3 R -norbornene AA present in peptide2 induces a more stable secondary structure with respect to the 1 S 2 S 3 S -isomer present in peptide1 .